Analisis Perencanaan Laba Melalui Perhitungan Break Even Point (BEP) Dari Kekreativan Mahasiswa Universitas Victory Sorong Berupa Taplak Meja Rajutan Benang Bermotif Honai - Boari , Sriani; Kewetary , Novelia; Montoh , Zerent Gabriel; Ahmad , Nardin; Lahallo, Fensca F. (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2024)
This study aims to provide information to the public regarding the definition, use, purpose and calculation method of Break Even Point (BEP) analysis both in Units and Rupiah in the sale of Yarn Knitted Tablecloth in Sorong City. By knowing the break-even point, we can determine the amount of expenses and income according to the target we want to achieve. The location of this research is located at Victory Sorong University, Southwest Papua. The location was chosen because of its role as a trading center. This study uses statistical analysis to process sales data and calculate BEP. This study uses a quantitative descriptive method. The results of this study show that the calculation of BEP in the sales unit of Yarn Knitted Tablecloth at Victory University Sorong. In July 2024, the break-even point was at 2.36 units with a sales level of Rp. 591,216.22 and during January 30 units were sold, the revenue was Rp. 7,500,000, then the profit level was Rp. 4,090,000. then the profit plan in August 2024, showed an increase in sales capacity to 40 units with a gross revenue of Rp. 10,000,000, the profit obtained was Rp. 5,590,000. The break-even point was at 2.36 units with sales of Rp. 589,225.59. The results of this study show that profit planning has increased in August.